DISTRIBUSI NILAI TAMBAH DALAM RANTAI NILAI KAYU SENGON (Paraserianthes falcataria) DARI KABUPATEN PATI, JAWA TENGAH, INDONESIA - Nunung Parlinah; Setiasih Irawanti; Aneka Prawesti Suka; Kirsfianti Linda Ginoga (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Community forests play an important role in household income and local economic activity. This research aims to study the timber value chain of  sengon (Paraserianthes falcataria) from Pati regency and specifically to identify the actors involved, understand the Paraserianthes falcataria distribution of  added value and formulate strategies to increase the added value for smallholders. The method used is value chain analysis involving 21respondents consisting of  individual and group respondents. The results reveal that the value added generated within the timber value-chain of  sengon are unevenly distributed among the actors. The smallholders who have direct access to the industry obtained better financial returns than smallholders who sell timber through middleman. Several strategies recommended to increase the value added for smallholders are improving capacity of  farmers and farmers group, building market information to unlock market access and creating partnership between farmers or farmers group with industries.